Effect of Biodiesel B100 and Ethanol Blends on the Performance of Small Diesel Engine - Firdiansyah, Alfian; Ilminnafik, Nasrul; Triono, Agus; Kustanto, Muh Nurkoyim (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
A small diesel engine is a machine that has high efficiency but causes a high level of pollution. The most widely used fuel so far is fossil energy which is unrenewable energy. The fruit of the Calophyllum inophyllum plant has great potential to be developed as alternative energy for small diesel engines. In this study, the test fuel used was D100, B100, E5, E10, and E15. The small engine diesel used TG-R180 Diesel with a compression ratio of 20:1 at engine turns 1500, 1800, 2100, and 2400 rpm, and the braking load at a constant prony disc brake is 1,5 kg/cm2. The result of the study using E10 fuel can improve engine performance and can reduce the opacity of the exhaust gas. The highest power in the D100 fuel at 2100 rpm is 8,06 PS. The highest thermal efficiency of E10 fuel is 50,29%. The use of Calophyllum inophyllum biodiesel (B100) can reduce exhaust gas opacity in small diesel engines when compared to the use of D100. E10 fuel has the lowest exhaust gas opacity rate of 4,1%.